The Influence of Steel Wool Fiber Length on The Characteristics of The Particle Board - Ramadhan, Fikri; Ula, Shofiatul; Sunardi (Talenta Publisher, 2024)
The use of wood powder can be reduced by a mixture of cinnamon, bamboo powder, and steel wool as a filling of the composite particle board. The length of steel wool in this study was determined by the size, i.e. 2, 4, and 6 mm. The composite composition comparison was 30% cinnamon powder, 30% bamboo Powder, 1% wool steel, 29% PVAc, and 10% epoxy resin. Compression process using the cold press single punch method for 2 hours then post curing process at a temperature of 150 oC for 1 hour. The results of this study show that steel wool length influences the characteristics of the particle board, both physical properties, mechanical properties, and morphological structure.